2022
DOI: 10.3389/fnana.2022.813841
|View full text |Cite
|
Sign up to set email alerts
|

Beta3Gn-T7 Is a Keratan Sulfate β1,3 N-Acetylglucosaminyltransferase in the Adult Brain

Abstract: Keratan sulfate (KS) glycan is covalently attached to a core protein of proteoglycans. KS is abundant in neuropils and presents densely in close proximity to the perineuronal region of the perineuronal net-positive neurons in the adult brain under physiological conditions. We previously showed that the synthesis of KS positive for the R-10G antibody in the adult brain is mediated by GlcNAc-6-sulfotransferase 3 (GlcNAc6ST3; encoded by Chst5). Deficiency in both GlcNAc6ST3 and GlcNAc6ST1, encoded by Chst2, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although B3GnT3, 4 and 9 showed some polyLacNAc synthesis activity towards LRP6, albeit lower than B3GnT2, they either had no significant effect (B3GnT4) or an inhibitory effect (B3GnT3 and 9) on LRP/Wnt signalling ( Figure S3c ). Interestingly, B3GnT7, which is reported to synthesise keratin sulphate (KS) by adding N-acetylglucosamine to KS glycosaminoglycans [ 57 , 58 , 59 ], showed the strongest inhibition of LRP6/Wnt signalling of any family member and induced a weakly diffuse but large upshift of the upper LRP6 protein band together with a strong LEL signal ( Figure S3b,c ). Nevertheless, B3GnT7 failed to significantly alter B3GnT2-induced LRP6/Wnt signalling when compared to other members ( Figure S2c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although B3GnT3, 4 and 9 showed some polyLacNAc synthesis activity towards LRP6, albeit lower than B3GnT2, they either had no significant effect (B3GnT4) or an inhibitory effect (B3GnT3 and 9) on LRP/Wnt signalling ( Figure S3c ). Interestingly, B3GnT7, which is reported to synthesise keratin sulphate (KS) by adding N-acetylglucosamine to KS glycosaminoglycans [ 57 , 58 , 59 ], showed the strongest inhibition of LRP6/Wnt signalling of any family member and induced a weakly diffuse but large upshift of the upper LRP6 protein band together with a strong LEL signal ( Figure S3b,c ). Nevertheless, B3GnT7 failed to significantly alter B3GnT2-induced LRP6/Wnt signalling when compared to other members ( Figure S2c ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to B3GnT2 and 8, other members have been implicated in the synthesis of polyLacNAc chains, such as B3GnT3 [ 63 ], and we have also shown that B3GnT3, 4, 7 and 9 can synthesise polyLacNAc on LRP6. It remains unclear why B3GnT7, which is reported to be specific for sulphated LacNAc chains present in keratin sulphate glycosaminoglycans [ 57 , 59 ], should stain positive for the polyLacNAc selective lectin, LEL. Like B3GnT2, which recognises and elongates LacNAc disaccharides in conjunction with B4GalT family members, B3GnT7 elongates LacNAc disaccharides; however, the N-acetylglucosaminyltransferase activity of B3GnT7 is thought to be specific for GlcNAc-6-sulphated LacNAc-containing glycans [ 59 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein-tyrosine phosphatase receptor type z1 (Ptprz1)/phosphacan in PNNs contain low sulfation KS. Extension of the KS is undertaken with GlcNAc by β1,3 N -acetylglucosaminyltransferase (Beta3Gn-T) ( Takeda-Uchimura et al. 2022 ).…”
Section: Phosphacanmentioning
confidence: 99%
“…GlcNAc6ST2 and GlcNAc6ST3 are complementary to the synthesis of CL40-reactive sialylated sulfated glycans in the mouse pleural mesothelium. Since we previously showed that the synthesis of cerebral R-10G-positive KS in which the predicted minimum epitope is an asialo 6-sulfo di-LacNAc [ 4 , 5 , 6 , 7 ] is GlcNAc6ST-dependent and that GlcNAc6ST3 is a major GlcNAc6ST in the adult brain [ 8 , 9 , 10 ], we tested the possibility that R-10G-reactive KS is also present in the pleural mesothelium. The question of which GlcNAc6STs are responsible for the synthesis of R-10G-reactive glycans was elucidated as well.…”
Section: Introductionmentioning
confidence: 99%